Adding a top-up sample to the HILDA Survey - Wooden, M; Watson, N (My University, 2013)
Since its commencement in 2001, the Household, Income and Labour Dynamics in Australia Survey has become a much-used resource by researchers. Over the same time, the Australian population has evolved in a number of ways that the sample, even with ‘following rules’, cannot emulate. Most notable is the lack of recent immigrants arriving after 2001. A general population-wide top-up of the sample was added in 2011 which allows new population sub-groups to be represented and helps alleviate biases from non-random attrition. This article describes the methodology of the top-up sample, the response rates achieved and the representativeness of the combined sample.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology -- Sample; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Sample; Surveys and Survey Methodology